Español - Español; Español; Español (Ars Pharmaceutica (Internet), 1975)
Sixteen culture media were used to determine cristal formation. Among the culture media used to study calcium carbonate formation, it was concluded that a medium (BRC) with yeastextract and calcium chloride was better and with satisfactory results. It was first time reported that "stroncianite" casld be formed biologically.